The relationship of academic self-efficacy to academic performances of UiTM freshmen / Tey Hwei Choo …[et al.] - Choo, Tey Hwei; Kee, Kor Liew; Ramaiah@Rama, Angayar Kanni (Research Management Institude, 2005)
This study explored the influence of four factors, talent, effort, emotion and social context on the academic self-efficacy. It also examined the relationships between self-efficacy and freshmen’s academic performance. This study also investigated academic self-efficacy in relation to the location of the campus, programs, gender, the place of residence, previous achievement, family income, parents’ occupation and education level. Academic self-efficacy is defined as students’ judgements about their cognitive capabilities to accomplish a specific task or obtain specific goals. Studies show that students’ self-efficacy can affect their choice of course and activities, how much effort they expend and how long they persist in the face of difficulties. It has important implications for motivation and academic performance. A total of 399 freshmen from Universiti Teknologi Mara, Malaysia were surveyed by questionnaire in this study. The Freshmen’s Academic Self-Efficacy (FASE) Questionnaire consisted of 39 items was designed using 4-point Likert scale response apart from 12 socio-demographic items. The reliability coefficient of FASE was .7342, indicating that the items in the survey questionnaire were reliable. The academic performance was obtained from students’ GPA.The results indicated that there was no significant difference in the aspect of academic self-efficacy at p<.05 between gender. However, there was significant difference between Engineering and Business Studies program with mean score for Engineering higher than Business Studies at p<.05. Female engineering freshmen reported the highest academic self-efficacy than its male counterparts, followed by the male and female freshmen respectively from the Business Studies program. Previous school backgrounds significantly influenced Arau freshmen academic self-efficacy at p<.05 with students from Diploma UiTM scored higher in academic-self-efficacy. Parents’ education level and occupation significantly influenced freshmen academic self-efficacy at p<.05. The result showed that freshmen parents whose were educated and worked as professional have higher academic self-efficacy than those whose parents worked in clerical or manual sector. This study suggested that family background of the freshmen is an important variable in determining their academic self-efficacy.Emotion correlated strongly with academic self-efficacy followed by talent, effort and social context. The four factors, however, correlated positively but weakly to GPA. Overall, there was a positive but weak relationship between academic self- efficacy and GPA (r=.199, p<.01). This means that freshmen who scored higher in academic self-efficacy have slightly better academic results.Non-academic factors such as the socio-environment factors, parents’ background and freshmen emotion play important roles in determining students’ academic performance. This study proposes that the interacting forces of peers. parents and educators are important in shaping the attitudes of freshmen as well as determining their academic self-efficacy and academic performance